Female Mystics and the Divine Feminine in the Global Sufi Experience - Milani, Milad; Taheri, Zahra; Kars, Aydogan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book offers a specialized study focusing on the phenomenon of the female mystic and the divine feminine in the global Sufi experience. Drawing on classical and modern periods, it presents a considered approach to the topic from the disciplines of literature, history, religion, philosophy, language and linguistics, and anthropology. As each author offers their expertise in their respective fields, each article, therefore, whilst a standalone piece, contributes collectively to the multidisciplinary understanding of the female and the feminine in Sufi experience. The book addresses the topic from different points of view, showing the authors' interest in subjectivity, literary and artistic productivity, as well as notable figures of importance, but narrows the purview of its examination to case studies, historical periods, and philosophical concerns of relevance. Focused areas of inquiry include the economic power of Sufi women in history; the hierophanic dialectics of mystical Islamic poetry with regard to "the feminine" experience in Yunus Emre; the ontology of the sacred feminine and female mystic in classical Sufi poiesis; the mystical autochthonous presence in local Sufi praxis of Indonesia; reconfigurations of gendered understanding in Argentinian Sufism; and symbolism and spiritual psychology in Sufi cosmology. This book is an interdisciplinary publication that brings together an international host of scholars from around the world, including University of Amsterdam, University of St Gallen, University of Haifa, Western Sydney University, Monash University, and Australian National University.